The Association Between Plasma Osmolarity and In-hospital Mortality in Cardiac Intensive Care Unit Patients - Zhai, Guangyao; Wang, Jianlong; Liu, Yuyang; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2021)
Abstract Objectives: Plasma osmolarity is a common marker used for evaluating the balance of fluid and electrolyte in clinical practice and has been proved to be related to prognosis of many diseases. The purpose of this study was to identify the association between plasma osmolarity and in-hospital mortality in cardiac intensive care unit(CICU) patients. Method: All patients were divided into seven groups stratified by plasma osmolarity and group of 290-300mmol/L was used as reference group. Primary outcome was in-hospital mortality. Local weighted regression(Lowess) smoothing curve was drawn to determine the “U”-shaped relationship between plasma osmolarity and in-hospital mortality. Binary logistic regression analysis was performed to determine the effect of plasma osmolarity on the risk of in-hospital mortality. Receiver-operating characteristic (ROC) curve was applied to evaluate the sensitivity and specificity of plasma osmolarity. Result: 7060 CICU patients were enrolled. A “U”-shaped relationship between plasma osmolarity and in-hospital mortality was observed through Lowess smoothing curve. The lowest in-hospital mortality(7.2%) was shown in group of 290-300mmol/L. With group of 290-300mmol/L serving as reference group, both hyposmolarity(<280mmol vs 290-300mmol/L: 13.0% vs 7.2%) and hyperosmolarity(≥330mmol vs 290-300mmol/L: 31.6% vs 7.2%) had higher in-hospital mortality. After adjusting for possible confounding variables in binary logistic regression analysis, both hyposmolarity(<280mmol/L vs 290-300mmol/L: OR, 95% CI: 1.76, 1.08-2.85, P=0.023) and hyperosmolarity(≥330mmol/L vs 290-300mmol/L: OR, 95% CI: 1.65, 1.08-2.52, P=0.021) were independently associated with the increased risk of in-hospital mortality. ROC curves revealed a moderate ability to predict in-hospital mortality when plasma osmolarity was greater than 290mmol/L(area under curve, 95%CI: 0.655, 0.633-0.677). Moreover, length of cardiac intensive care unit(CICU) and hospital stay were prolonged in patients with hyposmolarity or hyperosmolarity. Conclusion: A “U”-shaped relationship between plasma osmolarity and in-hospital mortality was observed. Both hyposmolarity and hyperosmolarity were independently associated with the increased risk of in-hospital mortality.